Recovery of Mycobacteria from Heavily Contaminated Environmental Matrices - Ulmann, Vit; Modrá, Helena; Babak, Vladimir; Weston, Ross Tim; Pavlik, Ivo (Microorganisms, 2021)
For epidemiology studies, a decontamination method using a solution containing 4.0% NaOH and 0.5% tetradecyltrimethylammonium bromide (TDAB) represents a relatively simple and universal procedure for processing heavily microbially contaminated matrices together with increase of mycobacteria yield and elimination of gross contamination. A contamination rate only averaging 7.3% (2.4% in Cluster S; 6.9% in Cluster R and 12.6% in Cluster E) was found in 787 examined environmental samples. Mycobacteria were cultured from 28.5% of 274 soil and water sediments samples (Cluster S), 60.2% of 251 samples of raw and processed peat and other horticultural substrates (Cluster R), and 29.4% of 262 faecal samples along with other samples of animal origin (Cluster E). A total of 38 species of slow and rapidly growing mycobacteria were isolated. M. avium ssp. hominissuis, M. fortuitum and M. malmoense were the species most often isolated. The parameters for the quantitative detection of mycobacteria by PCR can be significantly refined by treating the sample suspension before DNA isolation with PMA (propidium monoazide) solution. This effectively eliminates DNA residue from both dead mycobacterial cells and potentially interfering DNA segments present from other microbial flora. In terms of human exposure risk assessment, the potential exposure to live non-tuberculous mycobacteria can be more accurately determined.